Studi fenomenologi: Pemaknaan going concern melalui pengelolaan keuangan dan pemasaran - Erna Lovita; Gatot Prabantoro (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
SMEs' main problem in Indonesia is maintaining going concerned or business continuity. This research is motivated by the East Java SME business phenomenon, TSR. This study aims to demonstrate TSR's ability to interpret going concerns as implemented through financial management and marketing. The research method uses an interpretation paradigm as an umbrella for research with a phenomenological approach. Researchers collected data in the field for two months using an interview, observation, and documentation approach. The data analysis phase uses an intentional analysis, epoche, dan eidetic reduction. The results showed that TSR owners value perseverance and piety in maintaining business continuity. Business continuity at TSR is achieved through financial and marketing management. Financial management at TSR reflects accountability, efficiency, and compliance with the law. TSR conducts market segmentation, builds customer loyalty, and creates the brand image in its marketing activities.